2022
DOI: 10.1186/s12974-022-02567-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylated tau mediates neuronal death by inducing necroptosis and inflammation in Alzheimer’s disease

Abstract: Background Progressive neuronal death is the key pathological feature of Alzheimer’s disease (AD). However, the molecular mechanisms underlying the neuronal death in AD patients have not been fully elucidated. Necroptosis reportedly activates and induces neuronal death in patients with Alzheimer’s disease (AD); however, the main mediators and mechanisms underlying necroptosis induction in AD remain elusive. Methods The function of hyperphosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…In 2017, Caccamo et al first reported that the activation of the RIPK1/RIPK3/MLKL necrosome contributes to neuronal loss in both human AD brains and the AD mouse model . The connection of necroptosis and p-Tau has been confirmed that p-Tau is the key initiator of necroptosis in cultured neuronal cells and in an Tg­(Prnp-MAPT*P301s)­Ps19Vle/JNju AD mouse model . For the mechanism, RIPK1 was reported to be highly expressed by microglial cells in human AD brains and significantly higher in sporadic human AD brains than in health people but not RIPK3 .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In 2017, Caccamo et al first reported that the activation of the RIPK1/RIPK3/MLKL necrosome contributes to neuronal loss in both human AD brains and the AD mouse model . The connection of necroptosis and p-Tau has been confirmed that p-Tau is the key initiator of necroptosis in cultured neuronal cells and in an Tg­(Prnp-MAPT*P301s)­Ps19Vle/JNju AD mouse model . For the mechanism, RIPK1 was reported to be highly expressed by microglial cells in human AD brains and significantly higher in sporadic human AD brains than in health people but not RIPK3 .…”
Section: Discussionmentioning
confidence: 88%
“…The above results indicate that SZM679 treatment rescues the damaged hippocampal structure of AD mice. It has been evidenced that hyperphosphorylated Tau (p-Tau) is the key initiator of necroptosis in cultured neuronal cells . The AD biomarkers (p-Tau and Tau) were then tested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( Liu et al, 2015 ; Sekerdag et al, 2018 ; Weiland et al, 2019 ; Hu et al, 2020 ; Dionísio et al, 2021 ). In Alzheimer’s disease, pTau can cause neuronal death by inducing necroptosis ( Dong et al, 2022 ), while introducing the gene of amyloid precursor protein (App) can enhance necroptosis ( Pang et al, 2022 ). In PD, fibrillar alpha-synuclein promotes the activation of neurotoxic astrocytes through RIP kinase signaling pathway ( Chou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%